Rancang Bangun Mesin Espresso dengan Sistem Pre-Charge Pneumatic - Dwi Istiyarno; Ikhwan Taufik; Herru Budi Santoso (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The development of technology in the world is growing rapidly, so that technology is able to make everything that is done faster and more effective, such as technology that is developing in the coffee industry. Manual espresso machines are done using human power, so there are limitations to the power needed to make espresso in large quantities at once and lack of time efficiency. This pneumatic system allows for more responsive pressure control compared to manual systems. The Pneumatic Pre-Charge (PCP) system is a system that utilizes natural resources as its main energy source in renewable energy systems such as air. The method used to achieve a more optimal manual espresso machine is to use an experimental research method to test the performance of the espresso machine designed from a combination of a PCP system through empirical data collection to measure how efficient the machine is. The design process produces a manual espresso machine design which can then be developed into a espresso machine. Testing was carried out as many as 210 cycles and was divided into 3 stages of testing, namely a 360 cc cylinder capacity with a pressure of 2700 psi capable of pressing an average of 70 times, showing that the coarser the grind size of the coffee powder used, the time and pressure required will be reduced by requiring a pressure of 35 psi. From the results of this study, further testing is needed on the use of a PCP system espresso machine to validate its usefulness in supporting the needs of making espresso in the coffee industry.